Claudin and pancreatic cancer - Wang, Chen; Wu, Na; Pei, Beibei; Ma, Xiaoyan; Yang, Wenhui (Frontiers in Oncology, 2023)
Due to the lack of timely and accurate screening modalities and treatments, most pancreatic cancer (PCa) patients undergo fatal PCa progression within a short period since diagnosis. The claudin(CLDN) family is expressed specifically as tight junction structure in a variety of tumors, including PCa, and affects tumor progression by changing the cell junctions. Thus far,many of the 27 members of the claudin family, including CLDN18.2 and CLDN4, have significantly aberrantly expression in pancreatic tumors. In addition, some studies have confirmed the role of some claudin proteins in the diagnosis and treatment of pancreatic tumors.By targeting different targets of claudin protein and combining chemotherapy, further enhance tumor cell necrosis and inhibit tumor invasion and metastasis. CLDNs can either promote or inhibit the development of pancreatic cancer, which indicates that the diagnosis and treatment of different kinds of CLDNs require to consider different biological characteristics. This literature summarizes the functional characteristics and clinical applications of various CLDN proteins in PCa cells, with a focus on on CLDN18.2 and CLDN4.